Short-term effects of empagliflozin on preventing contrast induced acute kidney injury in patients undergoing percutaneous coronary intervention, a randomised trial - Zeinab Sadat Hosseini; Mohammad Javad Jamili; Behzad Ensan; Ghazaleh Donyadideh; Bahram Shahri; Hamid Eshraghi; Susan Darroudi; Mohsen Moohebati (Scientific Reports)
Abstract Contrast-induced acute kidney injury (CI-AKI) is a prevalent cause of hospital-acquired renal impairment in patients undergoing intervention. Limited clinical trials explore SGLT2 inhibitors’ effects on CI-AKI. This study aimed to assess the short-term effect of empagliflozin- an SGLT2 inhibitor- in reducing CI-AKI incidence in PCI patients regardless of diabetes. This research conducted a double-blind randomized clinical trial involving 121 patients undergoing PCI referred to Ghaem Hospital, Mashhad, Iran from 2022 to 2023. Participants were randomly assigned to receive empagliflozin (10 mg daily) or a placebo, starting one day before PCI and continuing for two days post-procedure. Renal function parameters such as estimated glomerular filtration rate (eGFR), creatinine, cystatin C, and urea were evaluated. After the intervention, empagliflozin users exhibited a significant reduction in mean cystatin C levels compared to the placebo users across all age groups (< 50 years, 50–60 years, and > 60 years). Patients older than 60 showed significant improvements in mean changes of eGFR with empagliflozin. Patients with eGFR > 60 and 45 < eGFR < 60 had a significant increase in eGFR in the empagliflozin group. Mean changes in cystatin C levels were significantly reduced with empagliflozin in all eGFR levels (> 60, 45–60, and < 45). There was no significant difference in urea and creatinine levels between the two groups. Empagliflozin notably decreases CI-AKI incidence in PCI patients by improving renal function parameters such as eGFR and cystatin C. These benefits were observed across various age groups, particularly in middle-aged and elderly, and those with varying renal function levels.